Charlotte Mew: Poetics, Bodies, Ecologies - Bratton, Francesca; Girdwood, Megan; Riddell, Fraser (Palgrave Macmillan, 2024)
This collection of essays explores the life and works of the British poet and author of short stories Charlotte Mew (1869-1928). It represents the first volume dedicated solely to critical engagement with the full range of Mew’s poetry, fiction and essays. Mew moved within a remarkable range of literary and intellectual circles, from The Yellow Book in the 1890s to Bloomsbury’s Poetry Bookshop in the 1910s. As such, her work challenges traditional distinctions between literary periods and sits within the more expansive framework of the long nineteenth century and its legacies. Each chapter contextualises Mew’s oeuvre by examining her experiments with poetic and narrative genres in relation to her wider late Victorian and early modernist intellectual milieu. The volume draws together literary scholars working across the fields of poetry and poetics, decadence, modernism, ecocriticism and queer theory, while illustrating the particular stylistic and thematic complexities of Mew’s writing.